Synthesis of diverse indole libraries on polystyrene resin – Scope and limitations of an organometallic reaction on solid supports - Knepper, Kerstin; Vanderheiden, Sylvia; Bräse, Stefan (Beilstein Journal of Organic Chemistry, 2012)
The synthesis of diverse substituted indole structures on solid supports is described. The immobilization of nitrobenzoic acid onto Merrifield resin and the subsequent treatment with alkenyl Grignard reagents delivered indole carboxylates bound to solid supports. In contrast to results in the liquid phase, ortho,ortho-unsubstituted nitroarenes also delivered indole moieties in good yields. Subsequent palladium-catalyzed reactions (Suzuki, Heck, Sonogashira, Stille) delivered, after cleavage, the desired molecules in moderate to good yields over four steps. The scope and limitations are presented.
Keywords: chemical diversity; cross-coupling reactions; indole; Merrifield resin